2009
DOI: 10.1080/19361520903317295
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder in Young Children Exposed to Terrorism: Validation of the Alternative Diagnostic Criteria

Abstract: The need to adapt the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV, American Psychiatric Association, 1994) criteria for diagnosing posttraumatic stress disorder (PTSD) in young children is widely recognized, yet attempts to validate alternative criteria have been limited. We examined profiles of PTSD symptoms in 29 Israeli children directly exposed to terrorism and a comparison group of 25 unexposed children. Whereas only 7% of the exposed children met PTSD criteria according to the DSM, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Significant between-group differences in PTSD diagnosis and symptoms, using the Scheeringa et al (2003) criteria, were reported in an earlier part of the project (E. Cohen, 2006;Cohen & Gadassi, 2009). In the exposed group, 9 of 29 children met the criteria for PTSD compared with no children in the comparison group, χ 2 ) = 9.3, p < .01.…”
Section: Ptsd and Ptpmentioning
confidence: 83%
“…Significant between-group differences in PTSD diagnosis and symptoms, using the Scheeringa et al (2003) criteria, were reported in an earlier part of the project (E. Cohen, 2006;Cohen & Gadassi, 2009). In the exposed group, 9 of 29 children met the criteria for PTSD compared with no children in the comparison group, χ 2 ) = 9.3, p < .01.…”
Section: Ptsd and Ptpmentioning
confidence: 83%
“…The PTSD Semi‐Structured Interview for Infants and Young Children (Scheeringa et al.) back‐translated Hebrew version of this parent‐report scale was used in this study (Cohen & Gadassi, ). The scale consists of 31 items derived from the DSM‐IV PTSD criteria (intrusive recollection, avoidance/numbing, and hyperarousal) and includes new criteria with special sensitivity to developmental consideration in preschool children (e.g., new fears, new separation anxiety, and new aggressive behavior).…”
Section: Methodsmentioning
confidence: 99%
“…Cohen et al 35 2009 Terrorism Repeat Interpers. 1.34) Isr( 100 J o u r n a l P r e -p r o o f Quality Checklist for Prevalence Meta-Analysis Checklist to assess each study's quality.…”
Section: Figure 2 Forest Plot For Overall Prevalence Levels Using Optimal Diagnostic Criteria Applied In Each Studymentioning
confidence: 99%